2015
DOI: 10.1016/j.bpj.2015.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Structural Perspectives on the Evolutionary Expansion of Unique Protein-Protein Binding Sites

Abstract: Structures of protein complexes provide atomistic insights into protein interactions. Human proteins represent a quarter of all structures in the Protein Data Bank; however, available protein complexes cover less than 10% of the human proteome. Although it is theoretically possible to infer interactions in human proteins based on structures of homologous protein complexes, it is still unclear to what extent protein interactions and binding sites are conserved, and whether protein complexes from remotely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
(85 reference statements)
0
11
0
1
Order By: Relevance
“…Since the eukaryotic proteins are not exclusive to only one set of function, it has been perceived that most of the eukaryotic protein interactions are transient, having smaller interaction hotspot zones and have more planar binding sites consisting of more polar and aromatic residues. These properties of the eukaryotic protein interactions make them essential part of cell signaling pathways (Goncearenco et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since the eukaryotic proteins are not exclusive to only one set of function, it has been perceived that most of the eukaryotic protein interactions are transient, having smaller interaction hotspot zones and have more planar binding sites consisting of more polar and aromatic residues. These properties of the eukaryotic protein interactions make them essential part of cell signaling pathways (Goncearenco et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on PPI binding site properties go back several decades, and some of them reported an extensive similarity between protein interfaces even in the absence of sequence or structure similarity between proteins [1215]. Since the current coverage of the human proteome with protein structural complexes remains limited, and the number of novel PPI binding sites in the PDB database grows slower than the number of protein complexes [16, 17], different computational methods have been proposed to close this gap. It has been shown that protein interactions and binding sites for human complexes can be predicted from homologous protein structural complexes of another species [1820].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that protein interactions and binding sites for human complexes can be predicted from homologous protein structural complexes of another species [1820]. Such an inference approach may be supported by a recent work that examined the growth dynamics and evolutionary roots of PPI binding sites and found that a majority of binding sites could be traced back to the universal common ancestor of all cellular organisms [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Evolution and physicochemical properties of binding sites in biological units of homo-oligomers have been studied by clustering based on sequence and structure. 13 These structural and evolutionary studies have led to an interolog approach, wherein conserved structures of homologous pairs of interacting proteins across different organisms are exploited in the prediction of interface residues in homo-oligomeric proteins of unknown structure using their homologues of known structure. 14 The protein subunit interactions stabilises the interacting interfaces and prevents the formation of aberrant assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Oligomeric states, interface residues, and binding modes are known to be conserved in closely related homo‐oligomers. Evolution and physicochemical properties of binding sites in biological units of homo‐oligomers have been studied by clustering based on sequence and structure . These structural and evolutionary studies have led to an interolog approach, wherein conserved structures of homologous pairs of interacting proteins across different organisms are exploited in the prediction of interface residues in homo‐oligomeric proteins of unknown structure using their homologues of known structure .…”
Section: Introductionmentioning
confidence: 99%